Pemanfaatan Tiktok sebagai Media Pemasaran Brand Fashion Arkline untuk Menarik Konsumen Gen Z - Erwin Permana; Najma Nury; Sabrina Oktavia; Risya Zahrotul Firdaus (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Local fashion brands in Indonesia are gaining popularity due to their affordable prices and competitive quality compared to imported products. One successful example is Arkline, a local fashion brand that effectively uses digital marketing, particularly TikTok, to reach its target market. This study aims to analyze Arkline’s sales growth strategy using a qualitative descriptive approach. Data were collected through digital observations and official online sources. The findings reveal that TikTok is a highly effective platform for engaging Generation Z, who prefer visual, interactive, and authentic content. Arkline’s strategy includes creating trend-based videos, using TikTok Live for real-time interactions, and collaborating with influencers who have large followings. These methods help increase brand awareness, strengthen customer engagement, and drive purchasing decisions. Additionally, the TikTok Shop feature enables seamless in-app transactions, which boosts conversion rates. Overall, TikTok serves as a powerful tool for Arkline to build stronger relationships with consumers, expand its market reach, and stay competitive in the fashion industry. With the right digital marketing strategy and adaptability to current trends, local brands like Arkline can fully leverage TikTok’s potential as an effective platform in today’s digital era.